Addressing social issues in a universal HIV test and treat intervention trial (ANRS 12249 TasP) in South Africa: methods for appraisal - (:unkn) unknown (My University, 2015)
Background : The Universal HIV Test and Treat (UTT) strategy represents a challenge for science, but is also a challenge for individuals and societies. Are repeated offers of provider-initiated HIV testing and immediate antiretroviral therapy (ART) socially-acceptable and can these become normalized over time? Can UTT be implemented without potentially adding to individual and community stigma, or threatening individual rights? What are the social, cultural and economic implications of UTT for households and communities? And can UTT be implemented within capacity constraints and other threats to the overall provision of HIV services? The answers to these research questions will be critical for routine implementation of UTT strategies.Methods/design : A social science research programme is nested within the ANRS 12249 Treatment-as-Prevention (TasP) cluster-randomised trial in rural South Africa. The programme aims to inform understanding of the (i) social, economic and environmental factors affecting uptake of services at each step of the continuum of HIV prevention, treatment and care and (ii) the causal impacts of the TasP intervention package on social and economic factors at the individual, household, community and health system level. We describe a multidisciplinary, multi-level, mixed-method research protocol that includes individual, household, community and clinic surveys, and combines quantitative and qualitative methods.Discussion : The UTT strategy is changing the overall approach to HIV prevention, treatment and care, and substantial social consequences may be anticipated, such as changes in social representations of HIV transmission, prevention, HIV testing and ART use, as well as changes in individual perceptions and behaviours in terms of uptake and frequency of HIV testing and ART initiation at high CD4. Triangulation of social science studies within the ANRS 12249 TasP trial will provide comprehensive insights into the acceptability and
Keywords: African Research